A 'conversation' between Frank Land [FL] and Antony Bryant [AB] – : Part 2. (March 2021) - Bryant, Antony; Land, Frank
Part 1 of the 'conversation' offered important insights into a groundbreaking era for computer development – adding further detail to existing writings by Frank Land, the work of the LEO group in general, and extended accounts such as those by Ferry, Hally and Harding. This should have whetted the appetite for readers keen to know more, also prompting others to offer their own accounts. Part 2 moves on to Frank Land's subsequent activities as one of the founding figures of the Information Systems (IS) Academy, and his 'Emeritus' phase.